Dinamika Psikologis Konsumen: Peran Narsisme, Fanatisme, Kecemburuan Terhadap Niat Pembelian - Novebra, Alifa Amatulloh; Atmaja, Ferry Tema (Universitas Negeri Surabaya, 2024)
In the contemporary digital era, smartphones have transcended their conventional role as mere communication tools, assuming symbolic significance as markers of social status and lifestyle. Among these, the iPhone brand stands out as a symbol of prestige and elegance, marking a distinctive confluence of technological innovation and consumer behavior. This study delves into the multifaceted realm of consumer behavior within the context of iPhone purchases, scrutinizing the interplay of narcissism, brand fanaticism, brand jealousy, and purchase intention. Utilizing data gathered from 155 respondents who participated in iPhone acquisitions through an online questionnaire, the research employed Partial Least Square analysis via SmartPLS version 4 for comprehensive data analysis. The findings illuminate a positive correlation between narcissistic behavior and both brand fanaticism and brand jealousy. Furthermore, brand fanaticism demonstrates a positive influence on purchase intention. However, the analysis indicates no significant impact of the relationship between brand jealousy and narcissistic behavior on purchase intention. This study enriches our understanding of the intricate dynamics shaping consumer purchase intentions, offering valuable insights for the development of targeted marketing strategies tailored to the distinctive characteristics of iPhone consumers.